The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1016/j.rvsc.2015.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of Gleason-like grading system of canine prostate carcinoma in veterinary pathology practice

Abstract: A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPTA single primary growth pattern was observed in 28 cases, a secondary pattern in 11 cases and a tertiary pattern in 6 cases. Cribriform, solid and small acinar/ductal were the most common primary, secondary and tertiary morphological patterns, respectively.The highest Gleason score (GS10) was obtained in 46.7% of cases. Nine of 14 metastasizing cases were classified as GS10. Gleason pattern 5 was present in 33 of cases.This study suggests that the modified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 15 publications
1
32
0
3
Order By: Relevance
“…As such, cytology can be considered a reasonable non‐invasive diagnostic tool in light of suspicious imaging and clinical findings and can be followed by histopathology for confirmation diagnosis if the results are equivocal. Additionally, at present, it is difficult to establish the prognostic significance of different subtypes of canine PCs, though a canine Gleason score has recently been proposed . Similarly in human medicine, histopathology is able to identify high‐grade prostate intra‐epithelial neoplasm (HG‐PIN) and atypical small acinar proliferation as premalignant histopathologic lesions that raise concern for development of prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, cytology can be considered a reasonable non‐invasive diagnostic tool in light of suspicious imaging and clinical findings and can be followed by histopathology for confirmation diagnosis if the results are equivocal. Additionally, at present, it is difficult to establish the prognostic significance of different subtypes of canine PCs, though a canine Gleason score has recently been proposed . Similarly in human medicine, histopathology is able to identify high‐grade prostate intra‐epithelial neoplasm (HG‐PIN) and atypical small acinar proliferation as premalignant histopathologic lesions that raise concern for development of prostate cancer .…”
Section: Discussionmentioning
confidence: 99%
“…However, in a recent study 32 canine Gleason score has recently been proposed. 36 Similarly in human medicine, histopathology is able to identify high-grade prostate intra-epithelial neoplasm (HG-PIN) and atypical small acinar proliferation as premalignant histopathologic lesions that raise concern for development of prostate cancer. 37 A study on HG-PIN in dogs suggested that early events in the carcinogenesis of the prostate may occur similarly in the prostate of elderly, sexually intact dogs; 38 another study conducted on military dogs found that HG-PIN was present in 18 of 25 dogs (72%) with PC.…”
Section: Discussionmentioning
confidence: 99%
“…Dementsprechend steht in der Veterinärmedizin oft nur ein kleiner Teil des Tumors zur histologischen Untersuchung zur Verfügung. Dies limitiert die histologische Diagnose stark, da in nicht beprobten Anteilen der Neoplasie möglicherweise andere histologische Wachstumsmuster vorhanden sind [28].…”
Section: Diskussionunclassified
“…▶Tab. 2 Nachweis der BRAF-Mutation in Prostatakarzinomen (n = 35) in Abhängigkeit vom vorherrschenden histologischen Wachstumsmuster nach Palmieri und Grieco [28].▶Table 2 Detection of BRAF mutation in prostate carcinomas (n = 35) depending on the predominant histological growth pattern according to Palmieri and Grieco[28]. Signalement der Rüden mit verschiedenen Prostataerkrankungen, deren Proben auf das Vorliegen der BRAF-Mutation untersucht wurden.…”
unclassified
See 1 more Smart Citation